先化简,再求值先化简,再求值1、5ac-2a平方b+[3abc-(4ab平方-a平方b)],其中a=-2,b=-1,c=3.2、已知a+b=2,求2(a平方+3a-2b+2b平方)-(2a平方+4a-6b+4b平方)的值.

来源:学生作业帮助网 编辑:作业帮 时间:2018/10/17 13:39:44
先化简,再求值先化简,再求值1、5ac-2a平方b+[3abc-(4ab平方-a平方b)],其中a=-2,b=-1,c=3.2、已知a+b=2,求2(a平方+3a-2b+2b平方)-(2a平方+4a-

先化简,再求值先化简,再求值1、5ac-2a平方b+[3abc-(4ab平方-a平方b)],其中a=-2,b=-1,c=3.2、已知a+b=2,求2(a平方+3a-2b+2b平方)-(2a平方+4a-6b+4b平方)的值.
先化简,再求值
先化简,再求值
1、5ac-2a平方b+[3abc-(4ab平方-a平方b)],其中a=-2,b=-1,c=3.
2、已知a+b=2,求2(a平方+3a-2b+2b平方)-(2a平方+4a-6b+4b平方)的值.

先化简,再求值先化简,再求值1、5ac-2a平方b+[3abc-(4ab平方-a平方b)],其中a=-2,b=-1,c=3.2、已知a+b=2,求2(a平方+3a-2b+2b平方)-(2a平方+4a-6b+4b平方)的值.
先化简,再求值
1、5ac-2a^2b+[3abc-(4ab^2-a^2b)],其中a=-2,b=-1,c=3.
5ac-2a^2b+3abc-4ab^2+a^2b
=5ac-a^2b+3abc-4ab^2
当a=-2,b=-1,c=3时,
5ac-a^2b+3abc-4ab^2=5×(-2)×3-(-2)^2×(-1)+3×(-2)×(-1)×3-4×(-2)×(-1)^2=-30+4+18-8=44
2、已知a+b=2,求2(a^2+3a-2b+2b^2)-(2a^2+4a-6b+4b^2)的值.
2a^2+6a-4b+4b^2-2a^2-4a+6b-4b^2
=2a+2b
当a+b=2时,
2a+2b=2(a+b)=2×2=4

原式=5ac-2a方b+3abc-4ab方+a方b
=5ac-a方b+3abc-4ab方
带入-16